Assessment of the feed additive beta‐carotene (3a160(a)) for all animal species for the renewal of its authorisation (BASF SE, DSM Nutritional Products Ltd., Europe‐Asia GmbH, JYB Europe BV, NHU Europe GmbH) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Roberto Edoardo Villa; Giovanna Azimonti; Eleftherios Bonos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Ronette Gehring; Boet Glandorf; Maryline Kouba; Marta López‐Alonso; Francesca Marcon; et al. (EFSA Journal)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of beta‐carotene (3a160(a)) for the renewal of its authorisation as a nutritional additive for all animal species. The Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) concluded that the use of beta‐carotene in animal nutrition under the approved conditions remains safe for target species, consumers and the environment. Regarding user safety, the FEEDAP Panel concludes that beta‐carotene is not a skin and eye irritant and not a skin sensitiser. One preparation containing 10% beta‐carotene was shown not to be a skin sensitiser. However, no conclusions on the safety for the user can be done on any other preparations. The Panel concluded there is no need for assessing the efficacy of the additive in the context of the renewal of the authorisation.